The Role of the Southeast Asian Ministers of Education Organization (SEAMEO) in Promoting the Internationalization of Higher Education and Strengthening Educational Cooperation in the ASEAN Region (2015-2025) - Nova Royani Putri; Rizki Damayanti (Sean Institute, 2026)
This study analyzes the role of the Southeast Asian Ministers of Education Organization (SEAMEO) in promoting higher education internationalization and strengthening educational cooperation in the ASEAN region from 2015 to 2025. Using a qualitative method with a case study approach, this research collects data through documentation studies, in-depth interviews with key informants, and observation of SEAMEO activities. The findings indicate that SEAMEO has implemented various strategic programs including academic mobility, educational quality standardization, institutional capacity development, and facilitation of regional collaborative research. Significant achievements are evident from the increase in student participation in exchange programs from 15,000 to 45,000 students, development of over 200 joint degree programs, and increase in collaborative research publications reaching 500 international articles. Despite facing challenges of capacity gaps among countries, funding limitations, and institutional coordination complexity, SEAMEO demonstrates high adaptability in responding to global dynamics such as the COVID-19 pandemic and digital transformation. This study concludes that SEAMEO plays a vital role in creating an integrated regional higher education ecosystem, with positive prospects for developing more inclusive and sustainable cooperation in the future.